Conjugated proteins: structure, functions and metabolism - Krisanova, N. V.; Ivanchenko, D. G.; Aleksandrova, K. V.; Rudko, N. P.; Крісанова, Наталія Вікторівна; Іванченко, Дмитро Григорович; Александрова, Катерина Вячеславівна; Рудько, Наталія Петрівна (Zaporozhye state medical university, 2016)
This textbook is recommended to use for students of international faculty (the second year of study) for independent work at home and in class. It is created as additional manual for study of Biochemistry for students of international faculty.
Складні білки: структура, функції та метаболізм